Towards implementing exercise into the prostate cancer care pathway: development of a theory and evidence-based intervention to train community-based exercise professionals to support change in patient exercise behaviour (The STAMINA trial) - Sophie Reale; Rebecca R. Turner; Eileen Sutton; Stephanie J. C. Taylor; Liam Bourke; Dylan Morrissey; Janet Brown; Derek J. Rosario; Liz Steed (BMC, 2021)
Abstract Background The National Institute for Health and Care Excellence (NICE) recommend that men on androgen deprivation therapy (ADT) for prostate cancer should receive supervised exercise to manage the side-effects of treatment. However, these recommendations are rarely implemented into practice. Community-based exercise professionals (CBEPs) represent an important target group to deliver the recommendations nationally, yet their standard training does not address the core competencies required to work with clinical populations, highlighting a need for further professional training. This paper describes the development of a training package to support CBEPs to deliver NICE recommendations. Methods Development of the intervention was guided by the Medical Research Council guidance for complex interventions and the Behaviour Change Wheel. In step one, target behaviours, together with their barriers and facilitators were identified from a literature review and focus groups with CBEPs (n = 22) and men on androgen deprivation therapy (n = 26). Focus group outputs were mapped onto the Theoretical Domains Framework (TDF) to identify theoretical constructs for change. In step two, behaviour change techniques and their mode of delivery were selected based on psychological theories and evidence to inform intervention content. In step three, the intervention was refined following delivery and subsequent feedback from intervention recipients and stakeholders. Results Six modifiable CBEPs target behaviours were identified to support the delivery of the NICE recommendations. Nine domains of the TDF were identified as key determinants of change, including: improving knowledge and skills and changing beliefs about consequences. To target the domains, we included 20 BCTs across 8 training modules and took a blended learning approach to accommodate different learning styles and preferences. Following test delivery to 11 CBEPs and feedback from 28 stakeholders, the training package was refined. Conclusion Established intervention development approaches provided a structured and transparent guide to intervention development. A training package for CBEPs was developed and should increase trust amongst patients and health care professionals when implementing exercise into prostate cancer care. Furthermore, if proven effective, the development and approach taken may provide a blueprint for replication in other clinical populations where exercise has proven efficacy but is insufficiently implemented.